1998
DOI: 10.1200/jco.1998.16.5.1811
|View full text |Cite
|
Sign up to set email alerts
|

Phase I and pharmacokinetic trial of paclitaxel in patients with hepatic dysfunction: Cancer and Leukemia Group B 9264.

Abstract: If paclitaxel is used for patients with elevated levels of AST or bilirubin, dose reductions are necessary, and an increase in toxicity can be anticipated. The increased myelosuppression observed is at least partially because of altered paclitaxel pharmacokinetics in such patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
37
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(39 citation statements)
references
References 9 publications
2
37
0
Order By: Relevance
“…4,5 Such events often affect the disease response, and are associated with treatmentcourse delays, discontinuations and dose reductions. 6,7 Patients undergoing cytotoxic chemotherapy require careful assessment of their liver function before, during and after chemotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…4,5 Such events often affect the disease response, and are associated with treatmentcourse delays, discontinuations and dose reductions. 6,7 Patients undergoing cytotoxic chemotherapy require careful assessment of their liver function before, during and after chemotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…Supporting this possibility are the data of Yamamoto et al (5), who found independent correlation of docetaxel clearance with cytochrome P4503A4 activity, serum levels of ␣-1 acid glycoprotein, and baseline transaminase activity in patients with normal total bilirubin and hepatic transaminase levels. Like docetaxel, elevated bilirubin or transaminase levels correlate with reduced clearance of paclitaxel and paclitaxel metabolites, increased AUC, and greater toxic effects (11). However, unlike docetaxel, alkaline phosphatase, total bilirubin, and transaminase values within the normal range failed to predict toxicity of paclitaxel in our population.…”
Section: Discussionmentioning
confidence: 61%
“…Venook et al [31] prospectively studied the PKs of both the 24-hour and 3-hour infusions of paclitaxel in patients with hepatic dysfunction, and found that dose reductions were necessary in patients with elevated AST or bilirubin (cohorts: (a) AST 2ϫ ULN and bilirubin Ͻ1.5 mg/dl, (b) bilirubin 1.6 -3 mg/dl with any level of AST, and (c) bilirubin Ͼ3 mg/dl with any level of AST) to prevent myelosuppression and neutropenic sepsis-related deaths. Investigators found that, for a 24-hour infusion of paclitaxel, doses Ͼ50 -75 mg/m 2 were not tolerated by patients with liver dysfunction.…”
Section: Paclitaxelmentioning
confidence: 99%
“…Investigators found that, for a 24-hour infusion of paclitaxel, doses Ͼ50 -75 mg/m 2 were not tolerated by patients with liver dysfunction. For the 3-hour infusion, doses of 100 mg/m 2 could be given to patients with moderate liver dysfunction, but for patients with severe liver impairment (bilirubin Ͼ3 mg/dl), doses had to be reduced to 50 mg/m 2 [31].…”
Section: Paclitaxelmentioning
confidence: 99%